Development of E-Module Media on Learning to Make Body Proportion Images in Class X Fashion Design SMK Negeri 1 Buduran - Adani, Marsha Belinda; Rahayu, Imami Arum Tri; Arifiana, Deny; Mayasari, Peppy (Journal of Education Method and Learning Strategy, 2024)
Media Learning is an educational instrument to support the learning process. The purpose of this study is to determine the process of developing E-Module media, the feasibility level of E-Module media, and student learning outcomes after applying E-Module media to learning to make body proportion images. This research uses Research and Development (R&D) research with the ADDIE development model. The data collection technique used feasibility validation with 2 media validation experts and 2 material validations as well as tests by students in class X fashion with a total of 36 students. The data analysis technique used is an assessment of media feasibility and student learning outcomes.  The results of the E-Module media feasibility level research on learning to make body proportion images were declared very feasible with a score of 4.25. Student learning outcomes in learning to make body proportion drawings are shown with classical percentages of 97% complete and 3% incomplete. E-Module learning media with very feasible categories can improve student learning outcomes in learning to make body proportion images in class X of SMK Negeri 1 Buduran.